UPAYA PELESTARIAN BATIK ASLI PEKALONGAN DALAM RANGKA MEMPERTAHANKAN PENGAKUAN UNESCO SEBAGAI WARISAN BUDAYA INDONESIA DI KOTAMADYA PEKALONGAN - Sunaryo, Tejo Bagus; Roberta, Maria Elisabeth (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2015)
This paper is made so people care about the originality of batik as Indonesia’s cultural heritage, to create a sense of nationality, love the homeland and so that the legacy of this country will not taken by other country. This is so that batik will still be recognized by UNESCO and the world as Indonesia’s own cultural heritage. The sources for the making of this paper was from the internet and from the author’s knowledge, because the author has been living in Pekalongan for 14 years. Although Pekalongan is only a small town, but Pekalongan had a unique history and culture that only Pekalongan who have it. Keywords: Pekalongan, batik, culture, legacy, UNESCO